It looks to me like you are trying to show that $\lnot P(c)$ as a lemma, where you have made no assumptions about $c$. If that were provable, then it would follow that $\forall x ( \lnot P(x))$. But that's too strong -- you only want to show that $\exists x (\lnot P(x))$. (Convince yourself that $\forall x ( \lnot P(x))$ is not necessarily implied by $\lnot (\forall x ( P(x))$, perhaps by thinking of an example set of $x$s and predicate $P$.)
So your dilemma is that you need to get the correct $c$ somehow, in order to prove that $\exists x (\lnot P(x))$; but you only know that $\lnot \forall x. P(x)$, and there's no way to get a $c$ directly from that statement.
In a situation where you get stuck it's good to try proof by contradiction. So, instead of proving $\exists x (\lnot P(x))$ (we have no idea how to get $c$ to make this true), try proving
$$
\lnot \lnot (\exists x ( \lnot P(x))),
$$
by assuming $\lnot \exists x ( \lnot P(x)))$ and getting a contradiction.
The proof structure will look like this:
1. $\lnot ( \forall x ( P(x)))$
$\lnot \exists x ( \lnot P(x))$
...[fill in here]...
$\bot$
5. $\lnot \lnot \exists x (\lnot P(x))$
6. $\exists x (\lnot P(x))$ (double negation elimination from 5)
But you have to fill in the details for step 3. ...
above.
To do this, show as another lemma there that $\forall x (P(x))$. Proving this lemma will just rely on premise $2$, but may require some more nested reasoning$^1$. Then this lemma will get a contradiction with your original assumption $1$.
$^1$ To prove $\forall x ( P(x))$ we want to start from no assumptions and get $P(a)$. To do this, assume $\lnot P(a)$ and derive a contradiction, thus showing $\lnot \lnot P(a)$, then double negation to $P(a)$.